2020
DOI: 10.1136/bmjopen-2020-038089
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of sarcopenia and depressive mood in older community dwellers: a cross-sectional observational study in China

Abstract: ObjectiveWhether sarcopenia is detrimental to depression is still controversial, which may be due to the three components of the sarcopenia. Our objective was to define the correlation between depression and sarcopenia in older Chinese community dwellers.DesignThe study has a cross-sectional design.SettingThe study was conducted in Jiangsu, China.ParticipantsA total of 101 men and 149 women aged 60 years or older were recruited.Outcome measuresLean tissue mass was measured by dual-energy X-ray absorptiometry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 28 publications
4
28
0
Order By: Relevance
“…Many cross-sectional studies have found that adults with low handgrip strength were at increased risk of depression. [13][14][15][16] Furthermore, three prospective cohort studies conducted in different countries have also reported similar results: high handgrip strength can reduce the risk of depression. [17][18][19] Meanwhile, a recent meta-analysis showed that muscle strength has a positive impact on reducing depression, with a pooled OR of 0.85 (95% CI: 0.80-0.89).…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Many cross-sectional studies have found that adults with low handgrip strength were at increased risk of depression. [13][14][15][16] Furthermore, three prospective cohort studies conducted in different countries have also reported similar results: high handgrip strength can reduce the risk of depression. [17][18][19] Meanwhile, a recent meta-analysis showed that muscle strength has a positive impact on reducing depression, with a pooled OR of 0.85 (95% CI: 0.80-0.89).…”
Section: Introductionmentioning
confidence: 65%
“…Our study suggested that low handgrip strength is associated with a higher risk of depression, independent of The impact of handgrip strength on depression has been examined in several studies, mainly focusing on community dwelling adults from various countries. [13][14][15][16] In a crosssectional study with a total of 24,109 Chinese adults, the authors reported that male participants with the highest grip strength were not at a reduced risk of depression (OR=0.91; 95% CI: 0.78-1.07) compared to male participants with the lowest grip strength; however, this association of a reduced risk of depression was found in females. 14 Another study of adults aged 50 years and older reported that both females and males had a significantly reduced risk of depression in all grip strength quartiles, 2, 3, and 4, compared to those in the lowest quartiles.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the muscle mass of the participants was not evaluated. However, most of the previous studies reported a relationship between depression and impaired HGS or muscle performance [5,9,11,16,21] but not between depression and low muscle mass [12,19,20]. Here, we comment that the lack of motivation caused by depression might cause impaired physical performance tests.…”
Section: Discussionmentioning
confidence: 61%
“…Decreased physical activity [30,31], increased oxidative stress [32,33], increased falling risk, which caused immobility [34,35], malnutrition [4,36], and dysregulated hormonal cycles [37,38] were some of the common risk factors suggested [39] in the literature. While some articles in recent years report the relationship between sarcopenia components and depression [5,[14][15][16][17][18][19][20][21], some of them reported that there is no relationship between sarcopenia components and depression [9][10][11][12][13]. We think there are several points to discuss our results here.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation